Amino Acid Density and L-Threonine Responses in Ross Broilers - Kidd, M.T.; Virden, W.S.; Corzo, A.; Dozier, W.A.; Burnham, D.J. (International Journal of Poultry Science, 2005)
An experiment was conducted to determine the effects of feeding broilers diets differing in amino acid density during the finisher period. Also, the impact of L-threonine addition to high (H) or low (L) amino acid density diets was determined. Ross x 708 male broiler chicks were placed in floor pens and fed common diets from d 1 to 34 that met or exceeded NRC (1994) recommendations. From d 35 to 55, broilers were fed diets consisting of H (digestible Lys of 0.88%, TSAA of 0.69%, and Thr of 0.59%) or L (digestible Lys of 0.82%, TSAA of 0.64%, and Thr of 0.55%) amino acid density, with or without dietary L-threonine (9 replications each of 4 treatments). On d 55, live performance and carcass characteristics were determined. There were no interactions or L-threonine effects (P>0.05) on live performance or carcass traits of broilers. Body weight and feed intake did not differ due to amino acid density. Birds fed diets containing H amino acid density had higher (P< 0.05) breast meat yield (P = 0.06 relative to BW; P = 0.01 relative to carcass weight) and lower (P<0.05) feed conversion and percentage abdominal fat than birds fed diets with L amino acid density. Minimizing essential amino acid excesses through dietary L-threonine inclusion did not improve or adversely affect performance. An economic analysis indicated that decreasing amino acid density (H to L) in 35 to 55 d broilers resulted in an income loss of 0.10/live bird.